2021
DOI: 10.52810/tiot.2021.100035
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Diseases based on Machine Learning

Abstract: With the rapid development of artificial intelligence, it is very important to find the pattern of the data from the observed data and the functional dependency relationship between the data. By finding the existing functional dependencies, we can classify and predict them. At present, cardiovascular disease has become a major disease harmful to human health. As a disease with high mortality, the prediction problem of cardiovascular disease is becoming more and more urgent. However, some computer methods are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Sentence documents are texts, which fall under the category of unstructured data, so the general classification algorithm cannot directly handle them, which makes them one of the challenges in automatically determining the law that applies to a case. Automatically determining the relevant legal issues in a case is a multilabel classification problem as opposed to the traditional classification problem in DM (data mining) [ 4 ] because a case frequently can be applied to multiple legal provisions. A framework describes a group of words with a similar cognitive structure and a dominant semantic role.…”
Section: Introductionmentioning
confidence: 99%
“…Sentence documents are texts, which fall under the category of unstructured data, so the general classification algorithm cannot directly handle them, which makes them one of the challenges in automatically determining the law that applies to a case. Automatically determining the relevant legal issues in a case is a multilabel classification problem as opposed to the traditional classification problem in DM (data mining) [ 4 ] because a case frequently can be applied to multiple legal provisions. A framework describes a group of words with a similar cognitive structure and a dominant semantic role.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the degree of difference between the curves in Figures 4 and 5 , it can be seen that the prediction model [ 20 ] established by using the first 40 data in the vehicle speed series obtained from the experiment has a better prediction effect on the last 20 vehicle speeds.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Literature [ 19 ] puts forward two strategies of setting left-turn phase and left-turn waiting area at intersections to improve the traffic quality at intersections. Literature [ 20 ] found that the intersection conflict simulated by software or model is very suitable for the actual intersection conflict research. Literature [ 21 ] holds that the occurrence of traffic accidents is mainly caused by the driver's mistakes, and the driver carries out a series of driving actions for a certain purpose, but the original driving intention cannot be realized due to the operation mistakes.…”
Section: Related Workmentioning
confidence: 99%
“…The research community has applied various classifiers for CVDs prediction such as Logistic Regression [ 40 , 73 , 74 ], Support Vector Machine [ 40 , 73 , 74 , 75 , 76 , 77 ], Naive Bayes [ 40 , 73 , 75 , 76 ], Neural Networks (NN) [ 75 ], k-Nearest Neighbours [ 75 , 76 ], Decision trees (DT) [ 75 ], AdaBoost [ 77 ], Random Forests [ 40 , 73 , 74 , 75 ], Language Model (LM) [ 75 ] and Gradient Boosting (GB) [ 73 , 77 , 78 ]. In Table 11 , we demonstrate a brief description of recent studies.…”
Section: Discussionmentioning
confidence: 99%